Lean 4.0: the next wave of innovation in hospitality - Anuar, Azyyati; Sadek, Daing Maruak; Razali, Mohamad Azli (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
The advent of Industry 4.0 has revolutionized various sectors, blending advanced digital technologies with traditional industrial processes (Moraes et al., 2023). Among these, the hospitality industry stands to gain significantly from integrating Lean principles with Industry 4.0, often referred to as Lean 4.0 (Rauch et al., 2020). This combination promises to enhance efficiency, reduce waste, and improve customer satisfaction by leveraging data analytics, IoT, and automation (Qureshi et al., 2023). In this paper, we review how Lean 4.0 principles are being applied within the hospitality sector to drive operational excellence and sustainability. By examining case studies and empirical evidence, we aim to illustrate the transformative potential of Lean 4.0 in creating smarter, more responsive, and environmentally conscious hospitality businesses (Sapra, 2023).